PERAN BRAND IMAGE DAN ELECTRONIC WORD OF MOUTH SEBAGAI VARIABEL MEDIASI PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PROPERTI (STUDI KASUS PADA PERUMAHAN MARGAHAYU KENDARI) - Nita Septiani Rachman; Alida Palilati; Juharsah; Dzulfikri Azis Muthalib (JIM : Journal Of International Management, 2026)
This study aims to analyze the effect of digital marketing on property purchasing decisions, with brand image and Electronic e-WOM as mediating variables. The population of this study consisted of 302 consumers, with a sample of 172 respondents determined using the Slovin formula. The data analysis methods used were descriptive analysis and PLS with the assistance of the SmartPLS application. The results of the study indicate that digital marketing has a positive and significant effect on both brand image and e-WOM, but does not have a significant direct effect on purchasing decisions. Brand image also does not significantly affect purchasing decisions and is unable to act as a mediating variable in the relationship between digital marketing and purchasing decisions. In contrast, e-WOM is proven to have a positive and significant effect on purchasing decisions, and is able to act as a partial mediator in the relationship between digital marketing and purchasing decisions consumers. These findings indicate that digital marketing is more effective in influencing purchasing decisions indirectly through e-WOM rather than through brand image.